Drug-induced liver injury. Part I: Classification, diagnosis and treatment - Dorota M. Kozielewicz; Piotr Stalke; Julita Skrzypek (Clinical & Experimental Hepatology)
Drug-induced liver injury (DILI) is a growing clinical problem. Antibiotics remain the most common cause of DILI in Europe. Their clinical spectrum is very broad, from asymptomatic to acute liver failure. Currently, DILI is categorized as hepatocellular (R ≥ 5), cholestatic (R ≤ 2) or mixed (R = 2-5) injury based on the serum alanine aminotransferase (ALT)/alkaline phosphatase (ALP) ratio. DILI is a diagnosis of exclusion and requires a wide differential diagnosis. The most important step in management is discontinuation of the drug suspected of causing liver damage. The list of specific antidotes that eliminate the effects of hepatotoxins is unfortunately very short. In symptomatic treatment, glucocorticosteroids and ursodeoxycholic acid have been used in selected cases. Liver transplantation is an optional treatment in patients with acute liver failure.